2005
DOI: 10.1007/s00284-005-4545-2
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Nisin-Like Peptide Produced by a Strain of Lactococcus lactis Isolated from Fermented Milk

Abstract: An isolate of Lactococcus lactis from fermented milk was found to produce a bacteriocin peptide. The isolate could grow in a medium with an initial pH of 11.0, in which it produced the bacteriocin extracellularly at the highest level. The level of the bacteriocin in the medium increased in parallel to the bacterial growth and reached its peak during the late exponential phase; thereafter it plateaued. The bacteriocin had a broad antibacterial spectrum similar to that of nisin and inhibited several related spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
4
20
0
Order By: Relevance
“…Among all, several strains of Lactococcus lactis subsp lactis produced nisin with desirable stability and a broad spectrum of activity not only against closely related species but also towards some food-borne pathogens such as Listeria monocytogenes. Nisin has been approved as a GRAS food preservative and became as the most widely studied bacteriocin (1,10,20).…”
Section: Introductionmentioning
confidence: 99%
“…Among all, several strains of Lactococcus lactis subsp lactis produced nisin with desirable stability and a broad spectrum of activity not only against closely related species but also towards some food-borne pathogens such as Listeria monocytogenes. Nisin has been approved as a GRAS food preservative and became as the most widely studied bacteriocin (1,10,20).…”
Section: Introductionmentioning
confidence: 99%
“…Several culture media were designed to optimize both responses under evaluation, lowering the cost of growth medium (around 25-40%) when comparing with standard MRS and LAPTg broths. Other non-standard culture media containing conventional ingredients were employed to study the growth and bacteriocin production of different LAB, which were compared with our results ( [3,24], similar to the media proposed in this work ( Table 4). The reduction of the culture media cost obtained from our results is adequate for their application in the industrial production of microorganisms and bacteriocins.…”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless, the yield was compared to be lower than in cultures started with an initial pH of 11.0 with maltose as the carbon source. We previously reported that L. lactis strain W8 could also grow and produce bacteriocin in a medium with an initial pH of 11.0 [30]. The strain W8 was distinguishable from the strain CM1 based on 16S rDNA sequences, biochemical properties, antibacterial activities, and the stability of the bacteriocins.…”
Section: Discussionmentioning
confidence: 99%
“…However, P. acidilactici F + resistant to nisin of L. lactis ATCC 11454 was sensitive to bacteriocin of the strain CM1. Geobacillus thermoleovorans and P. putida were resistant to the bacteriocin of CM1 but were sensitive to that of the strain W8 [30]. It was reported that both nisin A and nisin Z retained their antibacterial activity after treatment with tyrpsin [38,39], whereas nisin Z of CM1 was sensitive to trypsin.…”
Section: Discussionmentioning
confidence: 99%